Regenerative biomarkers for Duchenne muscular dystrophy - Simon Guiraud; Kay E Davies (Neural Regeneration Research, 2019)
Skeletal muscle has an extraordinary capacity to regenerate after injury and trauma. The muscle repair mechanism is a complex process orchestrated by multiple steps. In neuromuscular disorders such as Duchenne muscular dystrophy (DMD), the pathological consequences of the lack of dystrophin and the loss of the dystrophin-associated protein complex are dramatic, with a progressive cascade of events, such as continual influx of inflammation, repeated cycles of degeneration and impaired regeneration. Thus, muscle regeneration is a hallmark of the disease and careful monitoring of regenerative processes with robust markers should provide useful information to the field. Since decades, several indices of regeneration such as centronucleation and fibre size have been commonly used. In the present review, we discuss the impaired regenerative process in DMD, the common and new indices of regeneration and their associated methodologies. We notably highlight the regenerative marker embryonic myosin as a robust indicator of muscle regeneration. We also describe new quantitative methodologies offering the possibility of using a panel of translational regenerative biomarkers to obtain a more complete view of the regeneration processes. Upregulation of utrophin, an autosomal and functional paralogue of dystrophin, is one of the most promising therapeutic strategies as it targets the primary cause of the disease and is applicable to all DMD patients regardless their genetic defects. As utrophin is a regeneration associated protein increased in dystrophic muscle, we discuss the correlation of utrophin levels after drug treatment with regeneration markers. The recent advances in technologies and complementary markers of muscle regeneration described in this review, provide an unprecedented opportunity to develop more robust utrophin DMD based strategies for all DMD patients.